Using Communicative Language Teaching to instruct ESL at the university level - Emon, Obaidul Rahman (Talenta Publisher, 2024)
The study of how people learn languages has always fascinated researchers and has been a constant source of inspiration for both teachers and linguists. Within the spectrum of changing teaching methods, Communicative Language Teaching (CLT) is a prominent approach that emphasizes the development of effective communication skills in learners. The global recognition of this organization grew rapidly since its establishment in the 1970s, fueled by the necessity for language learners to develop effective communication abilities. However, the implementation of this approach faces several challenges because of the discrepancies between educators and this method. Chomsky (1957) emphasizes that in the field of language acquisition, important aspects include vocabulary, sentence structure, sound patterns, and word formation. This differs from Hymes' (1971) claim, which includes aspects such as grammar, meaning, social context, and practical use of language. The theoretical frameworks proposed by Hymes (1971) and other scholars lead to a significant change in thinking, driving the progress of communicative language teaching in second language education. Unlike the Grammar-Translation method, the Communicative Language Teaching (CLT) method provides learners with more opportunities to develop their ability to communicate effectively. This method greatly emphasizes the active involvement of learners in the second language classroom, which is not commonly seen in traditional teaching approaches. This study thoroughly examines the use of Communicative Language Teaching (CLT) in the context of teaching English as a second language. This text specifically discusses the evaluation of the advantages and disadvantages of Communicative Language Teaching (CLT) compared to outdated teaching methods, the current trends observed in CLT, and the challenges faced in implementing it in a university setting. The purpose of this elucidation is to provide educators with a thorough understanding of CLT (Communicative Language Teaching) while also offering suggestions for incorporating CLT into the university setting. This includes guidance on organizing classroom activities and strategies for motivating students.